Proposing a National Ethical Framework for Animal Research in Iran - M Mobasher; K Aramesh; SJ Aldavoud; N Ashrafganjooei; K Divsalar; CJC Phillips; B Larijani (Tehran University of Medical Sciences, 2008)
Background: One of the domains of scientific activities is working on animals. Performing experiments on animals is permissible only with the purpose of obtaining necessary information for saving and improving life of human beings or animals. Principally, all religions believe that human life is more valuable than animal life and humans have a God-given authority over animals, but they should not be cruel to animals and cause their pain or suffering. Based on Islamic view points, although Allah has put the Man as the lord of all creatures, he has not the right to use other creatures for any conditions and does not respect their real statues. Because of the widespread use of experimental animals in our country, special ethical codes should be redefined for living conditions of experimental animals based on the present regulations in Iran and also other countries. Therefore, all our researchers should have enough information about ethical codes of treating experimental animals as well as Islamic principles in this regard.Methods: All Islamic and international sources related to treating animals and also valid international ethical guidelines were collected and classified in order to extract the aimed points. Then all extracted points were reviewed by experts familiar with Islamic and ethical rules of treating animals. Results: Finally the strategies for appropriate and complete implementation of the national ethical guidelines of animal research in Iran were suggested.Conclusion: It is obvious that the suggested principles are applicable only with appropriate planning of training courses based on the facilities and needs of our country.